Promotion and Development of E-Marketing for Agricultural Community Enterprises in Talu Klang Thung Subdistrict Mueang District Tak Province: Promotion and Development of E-Marketing for Agricultural Community Enterprises in Talu Klang Thung Subdistrict Mueang District Tak Province - Pantana, Kattareeya; Wongrerkdee, Chakkapan; Naknarin, Thanaporn (RATANABUTH JOURNAL, 2025)
The Kaset Phan Suek Community Enterprise engages in agricultural production but has faced challenges in generating significant income due to a lack of knowledge in modern marketing strategies. Recognizing the importance of digital marketing, the group aimed to develop an electronic marketing system. This research was conducted to study development approaches, create an appropriate electronic marketing system, and evaluate user satisfaction with the system, tailored specifically for the community enterprise in Taluk Klang Thung Subdistrict, Mueang District, Tak Province. The process involved collecting and analyzing product data and designing a marketing system that aligns with the community's needs and the knowledge acquired from the study. A group of 30 enterprise members was selected through purposive sampling to test the system. The results revealed that participants regularly used smartphones and online platforms to purchase goods, indicating a readiness for digital solutions. The developed system was found to be highly suitable, with a satisfaction score averaging 4.56, which is considered very good.